Analisis Tingkat Pelayanan Service Kendaraan dan Penjualan Produk Sepeda Motor dengan Service Quality - Agung Pratama; Rizky Fauziah; Febby Madonna Yuma (J-Com (Journal of Computer), 2021)
Abstract: Based on available data, it is known that motorcycle sales at Panca Prima Abadi Dealers fluctuate every year. This resulted in several types of motorcycles that did not reach the sales target and affected operating income. The Panca Prima Abadi dealer realized that customers would return to buy motorcycles if they received good service. There are some customers who feel that the quality of service is relatively low so that in solving problems that cannot be solved optimally. The problem of vehicle service quality is supported by evidence of the changing number of customers who have performed service for the last 3 (three) years. To overcome this problem, a decision support system is made that will make it easier for Panca Prima Abadi Dealers to find out how the quality of motorcycle service has been provided to customers so far. Based on the calculation of the analysis of the level of service vehicle service and sales of motorcycle products using the Service Quality method, it can be concluded that the vehicle service has a "satisfied" predicate with a percentage value of 79.17% and a "very satisfied" predicate has a percentage value of 20.83% and product sales have a percentage value of 20.83%. the "satisfied" predicate gets a percentage value of 81.25% and the "very satisfied" predicate gets a percentage value of 18.75%. Keywords: Vehicle Service, Product Sales Service, Service Quality  Abstrak: Berdasarkan data yang ada diketahui bahwa penjualan sepeda motor di Dealer Panca Prima Abadi mengalami fluktuasi setiap Tahunnya. Hal ini mengakibatkan ada beberapa tipe sepeda motor yang tidak mencapai target penjualan dan mempengaruhi pendapatan usaha Pihak Dealer Panca Prima Abadi menyadari bahwa pelanggan akan kembali membeli sepeda motor jika mendapatkan pelayanan yang baik. Ada beberapa pelanggan yang merasa kualitas pelayanan yang relatif rendah sehingga dalam penyelesaian permasalahan yang belum dapat diselesaikan secara maksimal. Permasalahan kualitas pelayanan service kendaraan didukung oleh bukti jumlah pelanggan yang melakukan service selama 3 (tiga) tahun terakhir yang berubah-ubah. Mengatasi masalah tersebut maka dibuat suatu sistem pendukung keputusan yang akan memudahkan Dealer Panca Prima Abadi untuk mengetahui bagaimana kualitas pelayanan service sepeda motor yang telah diberikan kepada pelanggan selama ini. Berdasarkan perhitungan analisis tingkat pelayanan service kendaraan dan penjualan produk sepeda motor dengan metode Service Quality dapat disimpulkan bahwa service kendaraan memiliki predikat “puas” mendapat nilai persentase 79,17% dan predikat “sangat puas” mendapat nilai persentase 20,83% serta penjualan produk memiliki predikat “puas” mendapat nilai persentase 81,25% dan predikat “sangat puas” mendapat nilai persentase 18,75%. Kata Kunci: Pelayanan Service Kendaraan, Pelayanan Penjualan Produk, Service Quality